PENGARUH MODEL PEMBELAJARAN INTERAKTIF PICTURE AND PICTURE TERHADAP MOTIVASI BELAJAR SISWA PADA SUBTEMA AKU DAN CITA-CITAKU KELAS IV SD NEGERI LAMPEUNEURUT - Risma Yulisa; Intan Safiah; Suci Fitriani (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine the effect of Picture and Picture Interactive Learning on students' learning motivation in the Sub-theme I and My Goals in the fourth grade of SD Negeri Lampeuneurut. This study uses a quantitative approach. The sample of this study was grade 4 students, totaling 61 students. The method of data collection was carried out by tests and motivation scales, the results of the research used hypothesis testing with the help of SPSS version 22. Previously, hypothesis testing, homogeneity and normality were tested with homogeneity of 0.000 below 0.05, meaning the data is homogeneous. While the results of the normality test are 0.200 0.05, the information is normal. The results of hypothesis testing from the test with an R value of 0.729. While the value of R Square is 0.729, which means that students' learning motivation has an effect of 0.532% on learning outcomes using the Picture and Picture Interactive learning model. Because the value of sig 0.05, it tends to be concluded that H0 is rejected and Ha is recognized. Thus, it is stated that there is an effect of the Endless Picture Intelligent learning model on students' learning motivation in the Sub-theme I and My Goals for the fourth grade of SD Negeri Lampeuneurut. In the book theme 6 sub 1 learning 2.